1986
DOI: 10.1159/000284443
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Findings in Chronic Anal Pain

Abstract: The psychological characteristics of 21 patients suffering from chronic anal pain were studied. They underwent a clinical interview and completed the Eysenck personality questionnaire, the Zung self-rating depression scale and an analogue scale for the assessment of perceived pain. Data derived from the self-rating scales were compared with those obtained from a matched control group afflicted with fissure-in-ano. The pain patients reported higher scores for neuroticism, psychoticism, depression and perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Recent empirical studies in medical settings have reached the similar conclusion that patients who overreport somatic complaints are likely to exhibit personality characteristics associated with N (Barsky & Klerman, 1983;Chaturvedi & Bhandari, 1989;deLeon, Saiz-Ruiz, Chinchilla, & Morales, 1987;Jensen, 1988;Katon, Ries, & Kleinman, 1984;Magni, DeBertolini, Doli, & Infantino, 1986;Pilowski, Smith, & Katsikitis, 1987;Quill, 1985;Slavney, Teitelbaum, & Chase, 1985;Smail, 1970).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Recent empirical studies in medical settings have reached the similar conclusion that patients who overreport somatic complaints are likely to exhibit personality characteristics associated with N (Barsky & Klerman, 1983;Chaturvedi & Bhandari, 1989;deLeon, Saiz-Ruiz, Chinchilla, & Morales, 1987;Jensen, 1988;Katon, Ries, & Kleinman, 1984;Magni, DeBertolini, Doli, & Infantino, 1986;Pilowski, Smith, & Katsikitis, 1987;Quill, 1985;Slavney, Teitelbaum, & Chase, 1985;Smail, 1970).…”
mentioning
confidence: 96%
“…In reviewing this history, Zoccolillo and Cloninger (1986) discussed how in 1682 Syndenham concluded that somaticizers exhibit the personality characteristics of dysphoria and labile mood, in 1902 Kraepelin suggested that somaticizers have a disturbance of "emotional attitude," and in 1909 Savil wrote that somaticizers exhibit a marked emotional instability. Recent empirical studies in medical settings have reached the similar conclusion that patients who overreport somatic complaints are likely to exhibit personality characteristics associated with N (Barsky & Klerman, 1983;Chaturvedi & Bhandari, 1989;deLeon, Saiz-Ruiz, Chinchilla, & Morales, 1987;Jensen, 1988;Katon, Ries, & Kleinman, 1984;Magni, DeBertolini, Doli, & Infantino, 1986;Pilowski, Smith, & Katsikitis, 1987;Quill, 1985;Slavney, Teitelbaum, & Chase, 1985;Smail, 1970).…”
mentioning
confidence: 96%
“…For example, in addition to consistent findings that chronic pain patients have unusually high rates of depression, anxiety, and other psychological disorders that can be regarded as secondary to the painful state, chronic pain patients also tend to have histories of psychological disorders that predate pain onset and tend to meet diagnostic criteria for personality disorders: by definition personality disorders have early onset (usually late adolescence), are chronic, and for these reasons may be presumed to predate pain onset in most cases (Fishbain et aZ., 1986;Magni et aL, 1986). Similarly, as a group, chronic pain patients have consistently been observed to have higher scores on measures of 'neuroticism' and other variables that define vulnerability to psychopathology (Moosbrugger & Schermelleh-Engel, 1991; Wade et aZ., 1992): scores on measures of neuroticism and related constructs are correlated with pain and affect ratings in response to painful stimulation (Affleck et al, 1992;Harkins et al, 1990;Tondo & Gill, 1975).…”
Section: Introductionmentioning
confidence: 99%